KEPEMIMPINAN TRANSFORMATIF BERBASIS NILAI-NILAI ISLAM DALAM MENGEMBANGKAN ASPIRASI AKADEMIK PESERTA DIDIK MADRASAH ALIYAH SWASTA - Zahdi, Zahdi (STKIP Pesisir Selatan, 2025)
This study aims to analyze the leadership strategy of madrasah heads in developing academic aspirations based on Islamic values in Private Aliyah Madrasahs. The focus of the research is directed at the efforts of madrasah heads in instilling Islamic spiritual values such as sincerity, trust, and ijtihad as the basis for the formation of an academic culture that is able to foster learning motivation, enthusiasm for achievement, and students' aspirations to continue their education to a higher level. This research uses a qualitative approach with a case study design at MAS Paradigma Palembang. The results of the study show that the leadership of madrasah heads plays an important role in building students' academic aspirations through three main strategies: (1) internalization of Islamic values in learning activities and exemplary; (2) the formation of a conducive and collaborative academic culture; and (3) providing academic motivation and rewards on an ongoing basis. This strategy has been proven to be able to foster students' awareness of the importance of education, increase their confidence, and strengthen their commitment to achievement. This research offers a new perspective in the study of Islamic educational leadership by emphasizing the role of Islamic value-based leadership as a transformative approach in shaping students' academic aspirations.